Strategi Survival Usaha Mikro Kecil Menengah Batik Tulis Pekalongan di Tengah Pandemi Covid-19 (Studi Kasus pada “Batik Pesisir” Pekalongan) - Mohammad Rosyada; Anah Wigiawati (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
The Corona virus pandemic is not just a health disaster, the virus known as Covid-19 has caused chaos in the economic sector. Not only large industries, the Corona virus pandemic has made MSME players in Indonesia nervous. The existence of MSMEs, whose role has contributed significantly to the economic rate, has not been affected by the Covid-19 outbreak. Pekalongan Coastal Batik as one of Pekalongan's written batik MSMEs has also felt the impact of this Covid-19. This research was conducted to find out how the survival strategy carried out by Batik Pesisir Pekalongan can still exist and survive in the midst of the Covid-19 pandemic that has hit Indonesia. This study uses a qualitative method with a case study approach. From the results of this study, it can be seen that in running its business, "Batik Pesisir Pekalongan" uses various strategies in dealing with the competition in the batik industry amid the Covid-19 pandemic. The competitive strategy is taken by differentiating products every week, innovation and creativity, implementing friendly and excellent service to consumers, while in the promotion strategy "Batik Pesisir Pekalongan" uses several promotional mixes such as advertising, sales promotion, public relations. (public relations) and publications, direct marketing (direct marketing), personal selling and also internet marketing such as the use of social media and shorby (business links).